Democracy for dinosaurs : a guide for young citizens - Brown, Laurene Krasny (Little, Brown and Company, 2020)
"Using accessible dinosaur characters and clear language, Democracy for Dinosaurs explores key civic values on every adult's mind and helps show young readers how the things they do every single day can be guided by principles we must share in a democratic society: freedom, fairness, the rule of law, equality, respect for free speech, and respect for the truth. By modeling accessible ways to practice being a good citizen, children will understand they are part of their country and that they have an important role to play."--Provided by publisher.